Otomatisasi Pengujian Sistem Informasi Koperasi Berbasis Web Menggunakan Teknik Equivalence Partitioning - Ivana; Muhammad Deva Ditgara; Anggi Febriana; Yeni Rahmawati; Ahmad Fauzi (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
The validation process carried out to determine the quality of the software is an understanding of software testing. Testing is intended to find out application output errors that result in the system not running properly. There are 4 types of Black Box testing including Pairwise Testing, Boundary Value Analysis, Equivalence Partitioning, and Error Guessing techniques. This technique has advantages and disadvantages according to the needs of the application being tested. The Equivalence Partitioning technique was chosen as a Black box test because it is in accordance with the needs of the web-based Cooperative Information System application, in this test is divided into 2 test ranges to be valid and invalid. Beginning with identifying, testing system functions, establishing research data and archives, designing experimental cases and testing, and documenting research results and research conclusions. The results of testing, that this software runs according to what has been tested. However, the test is only carried out with a number of sample forms, for the time being this device has no problems and runs well.